2016
DOI: 10.1002/2015rs005937
|View full text |Cite
|
Sign up to set email alerts
|

The observation and simulation of ionospheric response to CIR/high‐speed streams‐induced geomagnetic activity on 4 April 2005

Abstract: The ionospheric response to corotating interaction region (CIR)-induced geomagnetic activity on 4 April 2005 has been studied using in situ electron density measurements, ground GPS-total electron content (TEC) observations, and numerical simulations of the National Center for Atmospheric Research Thermosphere-Ionosphere-Electrodynamics General Circulation Model (TIE-GCM). The case study resulted that the ionospheric positive response occurred from high to low latitudes. The positive effect at low latitudes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…Note that the varying IMF Bz itself, especially for the weakly negative Bz, can also modulate the terrestrial ionosphere. Additionally, the HSS can lead to the enhancement of the ratio of atomic oxygen to molecular nitrogen number densities (O/N 2 ) by modulating the thermospheric circulation, and thus slightly contribute to the TEC increase of electron density at lower latitude, which is consistent with the study of Chen et al (2016). Overall, the maximum increase of TEC during the recovery phase of the August 2018 storm was about 2 TECU in the TIEGCM as shown in Figure 8b, which was significantly lower than the observation results (more than 10 TECU) at the EIA region.…”
Section: Discussionsupporting
confidence: 89%
“…Note that the varying IMF Bz itself, especially for the weakly negative Bz, can also modulate the terrestrial ionosphere. Additionally, the HSS can lead to the enhancement of the ratio of atomic oxygen to molecular nitrogen number densities (O/N 2 ) by modulating the thermospheric circulation, and thus slightly contribute to the TEC increase of electron density at lower latitude, which is consistent with the study of Chen et al (2016). Overall, the maximum increase of TEC during the recovery phase of the August 2018 storm was about 2 TECU in the TIEGCM as shown in Figure 8b, which was significantly lower than the observation results (more than 10 TECU) at the EIA region.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that during the recovery phase of the storms studied by Chen et al. (2016), there exist geomagnetic disturbances during the storm recovery phase (AE = ∼500 nT), resulting in a longer recovery of the thermosphere than in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…Using GUVI observations and TIEGCM simulations, Chen et al. (2016) showed that the storm‐induced decrease in O/N 2 at ∼300 km lasted for about 2 days during the storm recovery phase. In contrast, the O/N 2 increases at low latitudes could last for 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation